Tracing the vector - Anidrita Saikia (Annals of Medical Science and Research)
The initial theory of miasma and malnutrition being responsible for kala azar was dismantled by researchers who identified the causative parasite as Ancylostoma duodenale, suggesting the disease was naturally present in the human body. Further research even considered soil as a potential source of the febrile nature of kala azar, but eventually, investigations in the early twentieth century focused on insect vectors as the likely cause of transmission. These enquiries were advanced under the aegis of the Kala Azar Commission, which initially explored the possibilities of the bed bug and the biting midge as possible vectors. Finally, in 1942, after a search that spanned almost 50 years, it was conclusively established that the Phlebotomus argentipes sandfly was the vector.